PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS X MIA MAN 1 PEKANBARU - Wildaniah Nur Pakpahan; Atma Murni; Zulkarnain ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is based on the low the ability of student’s mathematical understanding of class X MIA MAN 1 Pekanbaru. This research was done in class X MIA of MAN 1 Pekanbaru at second semester of academic year 2015/2016. The purpose of this research is to determine the effect of the implementation Cooperative Learning Model Think Pair Square (TPS) to increase the ability of student’s mathematical understanding of class X MIA MAN 1 Pekanbaru. The type of this research is quasi-experimental with a design that is used is Non-equivalent Control Group Design. The sampling technique used was purposive sampling technique. This research involved two classes, namely samples that are subjected to the experimental class of the application of cooperative learning model Think Pair square (TPS) while the control group received treatment in the form of conventional learning. The instrument of collecting data in this study is pretest and posttest ability mathematical understanding. This study shows that the increase in the ability of students' mathematical understanding experimental class is better than the control class. Index increased ability of understanding mathematical experimental class at the high category while the control class in middle category. It can be concluded that cooperative learning model Think Pair Square positive effect of increasing the ability of student’s mathematical understanding class X MIA MAN 1 Pekanbaru at second semester of academic year 2015/2016.Key Word : The Ability Of Mathematical Understanding, Cooperative Learning Model Think Pair Square (TPS), Quasi-experimental Research